Family-based psychosocial interventions for adult Latino patients with cancer and their caregivers: A systematic review - Guan, Ting; Cook, Paz; Xu, Shenmeng; Ranzinger, Lisa Hart; Conklin, Jamie L.; Alfahad, Abdulrahman Abdulmuslih S.; Ping, Yu; Shieh, Karl; Barroso, Susana; Villegas, Natalia; Song, Lixin (Frontiers in Psychology, 2023)
Objective This review aimed to systematically examine the characteristics and outcomes of family-based psychosocial interventions offered to adult Latino patients with cancer and their caregivers. Methods We searched six databases from their inception dates through June 2022. Studies were eligible for inclusion if they (1) targeted both adult Latino patients diagnosed with cancer and their adult caregivers or reported subgroup analyses of Latino patients and caregivers; (2) included family-based psychosocial interventions; (3) used randomized controlled trial (RCT) or quasi-experimental designs; and (4) were published in English, Spanish or Portuguese. Members of our multidisciplinary team assessed the risk of bias in the reviewed studies using the Cochrane Collaboration's Risk of Bias Tool. Results Our database searches yielded five studies. The studies were conducted in the U.S. and Brazil. Three studies were RCTs, and two used quasi-experimental designs. The sample sizes ranged from 18 to 230 patient-caregiver dyads. These studies culturally adapted the intervention contents and implementation methods and involved bilingual interventionists. The interventions had beneficial effects on multiple aspects of psychosocial outcomes for both patients and caregivers. We also identified methodological limitations in the reviewed studies. Conclusions Findings from this systematic review help deepen our understanding of family-based psychosocial interventions for Latinos affected by cancer. The small number of psychosocial interventions focused on adult Latino cancer patients and their caregivers is concerning, considering that Latino populations are disproportionally burdened by cancer. Future research needs to design and evaluate culturally-appropriate interventions to support Latino patients and families who cope with cancer. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=274993, identifier CRD42021274993.